(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Hepatitis A (HAV) infection is caused by the hepatitis A virus which is transmitted through the fecal-oral route. Life long protective antibodies are present after infection. The number of cases of adult hepatitis A has progressively been increasing during the last several decades in Bangladesh. In addition, the pattern of age-specific seroprevalence of anti-HAV has changed with economic growth. The prevalence of anti-HAV in 20-40 year age range has declined rapidly during the last 3 decades. As a result, this age groups has a high risk for HAV infection and clinically overt hepatitis A is increasing in adolescents and adult. The aim of the present study were to assess whether the proportion of adults with acute HAV infection has been increasing over the years and analyze the seroprevalence of immunoglobulin M(IgM) anti- HAV antibodies in young adults below the age of 20 years as well as in cases of chronic liver disease. Sera collected from 530 patients with acute and chronic liver disease attends the Somorita Hospital Ltd. during the previous 2 years and 6 months (Jan. 2008- Jun. 2010) were tested for various serological markers of acute and chronic hepatitis. In addition, 530 normal healthy attendants of the patients above the age of 20 years were tested for IgM anti-HAV as controls. Of 530 patients with acute hepatitis (13.42%) were positive for immunoglobulin M. The patients who were IgM anti-HAV negative were found to be hepatitis B (106 patients), hepatitis C, (10 patients), hepatitis E (150 patients) and unclassified (273 patients). Although the frequency of HAV infection among young adult (< 20 age) had increased (33.33% to 42.35%) in the 2 years and 6 months period, the frequency of HAV infection among adults had also increased (15.38% to 28.13%) during the same period. This study should be helpful for the identification of high risk population for vaccination of hepatitis A. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13065 Bangladesh J. Sci. Ind. Res. 47(3), 309-312 2012